IMPLEMENTASI MODEL CREATIVE PROBLEM SOLVING UNTUK MENINGKATKAN PRESTASI PEMBELAJARAN PANCASILA DI SDN 29 DADOK TUNGGUL HITAM PADANG : Bahasa Indonesia - Nursi, M.; Darwianis, Darwianis; Pebriyenni, Pebriyenni; Sayuti, M.; Rachmana N, Mogastra (Study program PGSD FKIP Universitas Bung Hatta, 2025)
The low achievement of Pancasila learning in Phase C (Grade V) of the Odd Semester of the 2024-2025 Academic Year, in the Sub-element material